2013
DOI: 10.1002/j.2205-0140.2013.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘sliding sign’ in conjunction with sonovaginography: is this the optimal approach for the diagnosis of Pouch of Douglas obliteration and posterior compartment deep infiltrating endometriosis?

Abstract: Introduction: Endometriosis is a chronic peritoneal disease that may progress as a deep infiltrating lesion involving the posterior compartment of the pelvis. Efforts to improve pre‐operative knowledge of the location and extent of these lesions have resulted in the development of Transvaginal ultrasound (TVS) as the first‐line imaging modality for extra‐ovarian endometriosis. However, various techniques of TVS have been described in the literature for this purpose. Methods: In this review we will detail the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Preoperative recognition of these phenotypes of endometriosis would facilitate triage of these women to centers of excellence for higher-stage endometriosis, consistent with the recommendation of the WES 3,7,21 . Integrating the use of TVS to identify women with bowel DIE and POD obliteration into the clinical work-up of women in whom surgery for endometriosis is planned would improve patient counseling, enhance theater-list management and potentially reduce women's exposure to multiple laparoscopies, with the attendant operative risks and healthcare costs 7,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative recognition of these phenotypes of endometriosis would facilitate triage of these women to centers of excellence for higher-stage endometriosis, consistent with the recommendation of the WES 3,7,21 . Integrating the use of TVS to identify women with bowel DIE and POD obliteration into the clinical work-up of women in whom surgery for endometriosis is planned would improve patient counseling, enhance theater-list management and potentially reduce women's exposure to multiple laparoscopies, with the attendant operative risks and healthcare costs 7,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of POD obliteration could be useful as a triage tool for referring women to centers of excellence for optimal management of severe endometriosis. Recently, Reid et al .…”
Section: Introductionmentioning
confidence: 99%
“…POD obliteration has also been associated with bowel DIE 12 ; Khong et al 13 demonstrated that women with POD obliteration had a three-fold higher risk of having coexisting bowel DIE requiring bowel surgery than did those without POD obliteration. Thus, symptomatic women presenting with both POD obliteration and bowel DIE should have endoscopic surgery performed by an appropriately trained laparoscopic surgeon working within a multidisciplinary team environment that includes a colorectal surgeon 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…As done above, gel sonovaginography has not been used so far to assess cases of local cervical and vaginal disorders other than for posterior compartment deep infiltrating endometriosis in a few recently published studies. 13,14 Limitations of this study were that it was done by a single operator in a single center. Also, the number of cases was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Gel sonovaginography is well tolerated in an outpatient setting, requires a single operator, and can be performed at a single visit as an extension of regular transvaginal sonography. As done above, gel sonovaginography has not been used so far to assess cases of local cervical and vaginal disorders other than for posterior compartment deep infiltrating endometriosis in a few recently published studies 13 , 14 …”
Section: Discussionmentioning
confidence: 99%